2020
DOI: 10.1016/j.esxm.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sexual Functioning of Individuals Living in Turkey During the COVID-19 Pandemic: An Internet-Based Nationwide Survey Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 22 publications
2
46
0
2
Order By: Relevance
“…Some researchers have reported income change to accompany high distress and depression 7 and even declined sexual activity. 27 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers have reported income change to accompany high distress and depression 7 and even declined sexual activity. 27 …”
Section: Discussionmentioning
confidence: 99%
“…These authors showed the low incidence of depression and anxiety in sexually active men during the lockdown, suggested the prophylactic part of dynamic sexual life concerning mental stress, and recommended using sexual functioning as a marker of psychological health during this tough time. Li et al 29 studied the impact of lockdown on men’s sexual behavior in China, while Karsiyakali et al 27 evaluated the changes in sexual activity of both genders in Turkey under COVID-19. Both studies did not use validated questionnaires like IIEF-15, PEDT, or BDI-II, as was the case in this case report.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations